Metal-Free Oxidative C(sp3)–N Coupling by HBr and DMSO: A Novel Synthesis of 2,3-Dihydroquinazolin-4(1H)-ones - Rezaei, Narjes; Sheikhi, Ehsan; Ranjbar, Parviz Rashidi (Synlett, 2018)
A metal-free oxidative C(sp3)–N coupling process has been developed for the synthesis of 2,3-dihydroquinazolin-4(1H)-ones. The reaction between primary amines, isatoic anhydride, and benzylic alcohols in the presence of HBr in DMSO at 80 °C affords 2,3-dihydroquinazolin-4(1H)-ones in excellent yields. Under these reaction conditions, benzylic alcohols react with in situ generated bromodimethylsulfonium bromide to form alkoxysulfonium intermediates. These intermediates undergo an oxidative cyclization reaction with primary amines and isatoic anhydride to produce the title products.
Keywords: C–N bond formation; metal-free reactions; oxidative coupling; HBr in DMSO; 2,3-dihydroquinazolin-4(1H)-one